The Labor Market and Industrial Relations Environment: Policy Issues and Options in a Global Economy - Macaraya, Bach M. (Philippine Journal of Labor and Industrial Relations; Vol 24 (2004): Philippine Journal of Labor and Industrial Relations, 2021)
This paper aims to provoke discussions on the policy changes that should be adopted to align the Philippine labor administration with the new economic system. It focuses on the Labor Code as the main source of labor policies in the Philippines and offers an analysis on the effectiveness of the Labor Code and its relevance to the global economy. It tackles specific issues such as employment relations, security of tenure, minimum wage fixing, freedom of association, collective bargaining, outsourcing, assumption of jurisdiction and the eight-hour labor law. Options are raised by the author to make the Labor Code more responsive to the new economic system.